Il design organizzativo come metadesign (Muse, 2025)
Contemporary ecological crises, technological transitions, and global systemic tensions position organizational design as a strategic field for rethinking the foundations of design. This article conceptualizes organizational design as metadesign, understood as the design of the very conditions for design: a reflective practice that extends beyond the production of structures or processes to shape the epistemic, relational, and symbolic frameworks that enable all other design activities.Building on theoretical references ranging from second-order cybernetics to transformative approaches inspired by Teal models and sociocracy, the paper introduces the organizational compass, an operational framework developed within Ecosistemica. Structured around three dimensions (Why, How, What) and six operational domains (structure, decision-making, participation, information flows, resource distribution, and feedback cycles), the framework supports organizations in reflecting on, learning from, and redefining their practices in a coherent, situated, and participatory manner.Combining co-design, participant observation, and speculative design, the compass functions as an enabling device for deep organizational transformation. More broadly, the contribution situates organizational design within the debate on the future of organizations as cultural infrastructures that generate worldviews, power relations, and shared meanings. In this perspective, organizational design, conceived as the design of design, emerges as a crucial lever for fostering new forms of coexistence that are more equitable, reflective, and generative.
Keywords: Metadesign; Design organizzativo; Cibernetica di secondo ordine; Approccio sistemico; Organizational design; Second-order cybernetics; Systemic approach; Design for social change